The monitoring system of surgical textile in health services - Berendina Elsina Bouwman; Dulcelene de Sousa Melo; Heliny Carneiro Cunha Neves; Cleuzeni Pereira Bento; Anaclara Ferreira Veiga Tipple (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to report the implementation of a monitoring system of the operative field, surgical gown, and utilized fields as sterile barrier system of products for health, manufactured from cotton fabrics. Methods: technological innovation report of a monitoring system of the use and processing of surgical textiles in a medium-size hospital. Results: steps: planning, confection, exchange of the surgical textiles, monitoring, and 12 months of supervision. The new pieces were silkscreened with a black indelible marker. Final Considerations: the implemented system is practical, low cost, and easily manageable for the team, it favored the work process management, contributing to the quality and security of the textile used in health care, and being able to be implemented in other health services.